259 Effect of Telegram Videos on Anatomy Education Among 2nd Year Medical Students, University of Khartoum, 2021. (28th February 2022) - Ibrahim, A.; Elhassan, A.B.E.; Salman, M.; Mohammed, O.; Bashir, S.; Mohamed, N.; Ali, M.; Awad, K.; Abdelkarem, A.
Abstract: Aim: COVID-19 had major effect on the health and medical education. In order to oblige with the social distancing and quarantine, universities shifted to online learning. This study aimed to assess the effect of online education on anatomy DR (dissection room) teaching by the use of telegram software. Method: This was a cross-sectional, prospective interventional study, which was carried out among 2nd year medical students in University of Khartoum. Students undertook initial tests on the heart and anterior abdominal wall modules. Telegram videos, prepared by the author, on the anatomy of the heart and the anterior abdominal wall were distributed to students. Students took a second test after watching the videos. A total number of 41 students attended heart sessions and 40 students attended the anterior abdominal wall sessions were included. Results: The pre-test mean score for the heart and abdomen modules were 4.56 ± 2.335 and 6.15 ± 2.94, respectively. The post-tests means were 9.98 ± 2.877 and 8.95 ± 3.14, respectively. 90% and 75% of the students were satisfied with these videos, respectively. Conclusions: This study revealed that Telegram videos as a method of online teaching had a positive effect on the students' performance, which was evidenced by the significant improvement in student's scores after watching the videos. Additionally, most of the students were satisfied with the videos and give positive feedback.